ORTMR - Optimized Routing Techniques for Mobile Adhoc Network using Network Resources - et.al, S. Menaka, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A mobile ad hoc network (MANET) is an dynamic wireless communication network that can be formed solely of any pre-accessible infrastructure that each gadget can function as a router, sender and receiver. It is well known in these networks that devices can roam arbitrarily anyplace in the network without revealing any information. So the mobility creates a disconnection that is uncertain between devices, that makes a device separation for the period of time. These kinds of frequent disconnections produce changes in device links and may create unstable network connections. Due to the unstable network, devices may experience a loss of energy that constructs the poor network lifetime. In the proposed, ORTMR-MANET a route has been established using network resources with optimized techniques, the network focuses on reducing the delay to transmit the packets successfully and controls the network stability primarily based totally on the link life incremental. To obtain the required accuracy in path selection ORTMR uses the fuzzy neuron computation to verify the device parameters. In which the results produces the high throughput with minimum delay transmission.